Pyrolysis derived char from municipal and industrial sludge : impact of organic decomposition and inorganic accumulation on the fuel characteristics of char - Chanaka Udayanga, Withanage Don (2021)
A comprehensive study was conducted to evaluate the fuel properties of the char produced from pyrolysis of municipal sludge (MS) and industrial sludge (IS) at different pyrolysis temperatures (500-700 °C). A detailed characterisation of the char was performed to investigate the impact of the decomposition and the accumulation of organic and inorganic compounds during pyrolysis on the fuel properties of the derived char. Increase in pyrolysis temperature increased the fuel ratios especially in the MS-derived char. On the other hand, ash accumulation resulted in decreased higher heating values (HHVs). Dehydration and decarboxylation were the main reactions, which caused the decomposition of the organic compounds in raw sludge during pyrolysis. Thermogravimetric analysis results showed that high temperature pyrolysis could improve the thermal stability of the derived char. The accumulation of catalytic inorganic compounds improved the combustion reactivity of both the IS and MS-derived char. The MS-derived char showed higher slagging and ash fouling indices compared to the IS-derived char despite the lower ash content. However, slagging and ash fouling indices of the char were comparable to that of raw sludge samples. The results indicate that the accumulation and physicochemical transformations of heavy metals during pyrolysis process would not be significantly affected during combustion of the char. For practical application in combustion, the MS-derived char has a greater potential due to considerable HHVs, improved thermal stability, efficient combustion characteristics, lower heavy metals leaching and comparable ash related issues.